2008
DOI: 10.2527/jas.2007-0310
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting length of productive life in Swedish commercial sows1

Abstract: The objective of this study was to investigate factors that might influence the length of productive life in Swedish crossbred (Landrace x Yorkshire) sows. The data set consisted of 20,310 sows farrowing between 2001 and 2004 in 21 commercial piglet-producing herds. Productive life (PL) was defined as the number of days between first farrowing and removal or termination of data collection. In addition to the overall risk analysis of PL, another 4 longevity traits were analyzed (competing risk analyses): reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
67
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 15 publications
11
67
2
2
Order By: Relevance
“…All these herds bought their genetic material from the Swedish pig-breeding organization, Quality Genetics (QG; Hö rby, Sweden). Data from these 16 herds have also been included in a larger study (21 herds) investigating the longevity (Engblom et al, 2008) and removal pattern of crossbred (Landrace 3 Yorkshire) sows (Engblom et al, 2007). A detailed description of the 21 herds, covering housing system and management has been presented earlier (Engblom et al, 2007).…”
Section: Herdsmentioning
confidence: 99%
“…All these herds bought their genetic material from the Swedish pig-breeding organization, Quality Genetics (QG; Hö rby, Sweden). Data from these 16 herds have also been included in a larger study (21 herds) investigating the longevity (Engblom et al, 2008) and removal pattern of crossbred (Landrace 3 Yorkshire) sows (Engblom et al, 2007). A detailed description of the 21 herds, covering housing system and management has been presented earlier (Engblom et al, 2007).…”
Section: Herdsmentioning
confidence: 99%
“…A Swedish study (Engblom et al, 2008) showed that 9% of all cullings in conventional systems were due to lameness; and in US herds the proportion of sows culled in response to locomotive problems was 15.2% in 200615.2% in (USDA, 2007. In Danish herds lameness is again one of the main reasons for culling sows.…”
Section: Introductionmentioning
confidence: 99%
“…Although the impact of claw lesions on sow longevity, lameness (Anil et al 2007;Anil et al 2009) and increased risk of culling (Engblom et al 2008) is established, there are only sparse reports on their associations with reproduction efficiency parameters. Previous studies reported the association of heel lesions and wall cracks with decreased litter weight, increased pre-weaning piglet mortality and higher odds of stillborn piglets (Fitzgerald et al 2012;Pluym et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lameness is an animal-based welfare indicator (Welfare Quality ® consortium 2009) which reduces the productivity of a pig herd by reducing sow longevity and the number of pigs produced per sow per year due to increased involuntary culling rates of sows (Anil et al 2005;Engblom et al 2008). Some claw lesions were also associated with decreased litter weight, increased pre-weaning piglet mortality and higher odds of stillborn and crushed piglets (Fitzgerald et al 2012;Pluym et al 2013).…”
mentioning
confidence: 99%